Pastoral Influences on the Relief of Poverty and their Metrics (London Journal of Research In Humanities and Social Sciences, 2023)
I am writing this paper from two perspectives, one to argue whether public policy can reduce or end poverty and then to argue why it is appropriate for policy makers to try. I plan to use the conclusions to state avidly, poverty is not a fixed product of civilized life. To even try to believe this, we are taught, is a sin. Yet somehow our targets for eradicating poverty lag. I intend to look at the reasons we do not feel compelled to  use our rich amounts of time and resources to reduce the burden of poverty on the poor and create a modern population of more educated, stable, higher incoming earning persons, and how failure to succeed violates the spirit of government.
Keywords: think tanks network. liberal institutes. ideological battle. neoliberalism.